2008
DOI: 10.1002/chem.200701472
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Nanorafts of Calixarene Polyphosphonates

Abstract: The water-soluble calix[4]arene bearing p-substituted phosphonic acid groups is accessible in five steps in overall 62 % yield, with the hydrogen-bonding prowess of the acidic groups dominating its self-assembly processes. These include the formation of 3.0(3) nm and 20(2) nm nanorafts of the calixarene in water using spinning disc processing, stabilized by acetonitrile, and nanorafts in the gas phase ( Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
60
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 73 publications
(61 citation statements)
references
References 20 publications
1
60
0
Order By: Relevance
“…Previously p -phosphonic acid calix[n]arenes (n = 4, 5, 6 and 8) have been shown to form stable nano-arrays (nano-particles) or nano-rafts (n = 4) in the gas phase using MALDI-TOF-MS with around 20 calixarene units (18-30 kDa) per nano-array 10. As for the p -phosphonic acid calixarenes, nano-arrays are also observed in the gas phase for the alkylated p -phosphonic acid calix[4]arenes with successive peaks out to 15, 33 and 16 calixarene units for the methyl, butyl and octadecyl derivatives, 12-14 , respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously p -phosphonic acid calix[n]arenes (n = 4, 5, 6 and 8) have been shown to form stable nano-arrays (nano-particles) or nano-rafts (n = 4) in the gas phase using MALDI-TOF-MS with around 20 calixarene units (18-30 kDa) per nano-array 10. As for the p -phosphonic acid calixarenes, nano-arrays are also observed in the gas phase for the alkylated p -phosphonic acid calix[4]arenes with successive peaks out to 15, 33 and 16 calixarene units for the methyl, butyl and octadecyl derivatives, 12-14 , respectively (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…Recently we reported a series of new water-soluble calixarenes, which incorporate phosphonic acid groups on the upper rim with the lower rim devoid of substitution,10 with a similar synthesis of the p -phosphonic acid calix[4]arene, and some lower rim alkyl substituted analogues (including methyl and n-propyl), being simultaneously reported by Dziemidowicz et al 11. These p -phosphonic acid calix[n]arenes (n = 4, 5, 6 and 8) form supramolecular arrays both in solution and the gas phase which relates in part to the H-bonding capability of the phosphonic acid group,10 In the present paper we report the synthesis of p -phosphonic acid calix[4]arene substituted with a variety of alkyl group substitutions on the lower rim, namely methyl, n -butyl and n -octadecyl, in an attempt to decouple the effect of the H-bonding of the phosphonic acid groups with that of the lower rim OH groups, although they tend to favour cyclic intramolecular H-bonding.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously we have reported that a series of p -phosphonic acid calix[n]arenes (n = 4, 5, 6 and 8) form stable nano-arrays (nano-particles) or nano-rafts (n = 4) in the gas phase using MALDI-TOF-MS with around 20 calixarene units (18-30kDa) per nano-array 8. This has been extended to alkylated p -phosphonic acid calix[4]arenes with successive peaks out to 15, 33 and 16 calixarene units for the methyl, butyl and octadecyl derivatives respectively 9.…”
Section: Resultsmentioning
confidence: 99%
“…These calixarenes are water soluble, and form bi-layers in the solid state, held together by strong hydrogen bonding between the diprotic phosphonic acid groups, and in solution and the gas phase they can form nano-rafts 8. O-alkylation at the lower rim while maintaining the integrity of the phosphonic acid/phosphate groups has also been reported, for methyl, n -butyl and n -octadecyl chains 9.…”
Section: Introductionmentioning
confidence: 96%